Electric systems, dynamics, and stability with artificial intelligence applications - Momoh, James A. 1950- (Power engineering, 2000)
This work seeks to provide a solid foundation to the principles and practices of dynamics and stability assessment of large-scale power systems, focusing on the use of interconnected systems - and aiming to meet the requirements of today's competitive and deregulated environments. It contains easy-to-follow examples of fundamental concepts and algorithmic procedures.